Matching execution histories of program versions. - Zhang, Xiangyu
We develop a method for matching dynamic histories of program executions of two program versions. The matches produced can be useful in many applications including software piracy detection and several debugging scenarios. Unlike some static approaches for matching program versions, our approach does not require access to source code of the two program versions because dynamic histories can be collected by running instrumented versions of program binaries. We base our matching algorithm on comparison of rich program execution histories which include: control flow taken, values produced, addresses referenced, as well as data dependences exercised. In developing a matching algorithm we had two goals: producing an accurate match and producing it quickly. By using rich execution history, we are able to compare the program versions across many behavioral dimensions. The result is a fast and highly precise matching algorithm. Our algorithm first uses individual histories of instructions to identify multiple potential matches and then it refines the set of matches by matching the data dependence structure established by the matching instructions. To test our algorithm we attempted matching of execution histories of unoptimized and optimized program versions. Our results show that our algorithm produces highly accurate matches which are highly effective when used in comparison checking approach to debugging optimized code.
Keywords: Software; Programming languages; Processors; Debuggers; Software engineering; Testing and debugging; Tracing; Debugging aids; Algorithms; Measurement; Reliability; Debugging; Dynamic analysis; Execution traces; Piracy Detection